2007 International Workshop on Physics of Semiconductor Devices 2007
DOI: 10.1109/iwpsd.2007.4472573
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes with electrode potential in microtubules and nanowires of Polyaniline: An in-situ EC-AFM study

Abstract: Abstract-Polyaniline (PANI) changes its conformationand conductivity on alteration of its electrochemical state. In the present work, we have studied the morphological changes with electrode potential in microtubules and nanowires of PANI using in-situ electrochemical AFM (EC-AFM). About 15 to 20% change in dimensions was observed on changing the electrochemical state in H 2 SO 4 as the electrolyte. Such changes in microtubules and nanowires of PANI may find useful applications in actuation and sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In particular, by monitoring the surface morphology of diamond electrodes during the ferro-ferricianide redox reaction, it has been shown that diamonds electrodes do not undergo degradation during redox reactions [22]. When applied to conducting polymers, which are considered as "intelligent materials" able to react to external stimuli, most of the works related to the detection of their topographical evolution, caused by the transition from the doped to the undoped state [7,[23][24][25]. Indeed, they are generally synthesized by an electrochemical oxidation of the monomer, which induces a cationic character on the polymer backbone.…”
Section: Passive Probe Configurationmentioning
confidence: 99%
“…In particular, by monitoring the surface morphology of diamond electrodes during the ferro-ferricianide redox reaction, it has been shown that diamonds electrodes do not undergo degradation during redox reactions [22]. When applied to conducting polymers, which are considered as "intelligent materials" able to react to external stimuli, most of the works related to the detection of their topographical evolution, caused by the transition from the doped to the undoped state [7,[23][24][25]. Indeed, they are generally synthesized by an electrochemical oxidation of the monomer, which induces a cationic character on the polymer backbone.…”
Section: Passive Probe Configurationmentioning
confidence: 99%